Inhibition of TNF-α-Induced Inflammation by Sesquiterpene Lactones from Saussurea lappa and Semi-Synthetic Analogues - Choodej, Siwattra; Pudhom, Khanitha; Mitsunaga, Tohru (Planta Medica, 2018)
We investigated the tumor necrosis factor-alpha (TNF-α) inhibitory activity of sesquiterpenes from Saussurea lappa root extracts. According to the hexane and EtOAc extracts showing significant activity with IC50 values of 0.5 and 1.0 µg/mL, respectively, chromatographic fractionation of the extracts was performed and led to the isolation of 10 sesquiterpenes (1–10). Costunolide (1), a major compound, and dehydrocostus lactone (4) exhibited high efficiency in decreasing TNF-α levels, with IC50 values of 2.05 and 2.06 µM, respectively. In addition, sesquiterpene analogues were synthesized to establish their structure-activity relationship (SAR) profile. Among the semi-synthetic analogues, compounds 6a and 16 showed the most potent activity with IC50 values of 1.84 and 1.97 µM, respectively. More importantly, compound 6a showed less toxicity than costunolide and 16. These results provided the first SAR profile of sesquiterpene lactones and indicated that the α-methylene-γ-lactone moiety plays a crucial role in TNF-α inhibition. Additionally, the epoxide derivative 6a might represent a lead compound for further anti-TNF-α therapies, owing to its potent activity and reduced toxicity.
Keywords: Saussurea lappa; Compositae; TNF-α inhibition; inflammation; sesquiterpene lactones; structure-activity relationship; semi-synthetic analogues